A controlled comparison trial of the Collaborative Assessment and Management of Suicidality (CAMS) in an inpatient setting: Outcomes at discharge and six-month follow-up. (March 2017) - Ellis, Thomas E.; Rufino, Katrina A.; Allen, Jon G.
Abstract: This controlled comparison trial evaluated a suicide-specific intervention, the Collaborative Assessment and Management of Suicidality (CAMS), in an extended-stay psychiatric inpatient setting. Multiple outcomes were examined for 104 patients, half of whom received individual therapy from therapists trained in CAMS. The comparison group was selected from a larger pool through Propensity Score Matching to ensure comparability on age, sex, treatment program, number of prior suicide attempts, and severity of suicidal ideation. Results showed that a) all patients improved significantly across a wide range of measures, including depression, suicidal ideation, functional disability, and well-being; b) these gains were durable over a 6-month post-discharge period; and c) patients treated by a CAMS-trained individual therapist improved significantly more from admission to discharge across all measures. Differences between CAMS and non-CAMS patients were no longer statistically significant at 6-month follow-up, although statistical power was compromised due to attrition. Although replication studies are needed, these findings suggest that interventions specifically tailored for suicidal patients may have advantages compared to usual, intensive inpatient treatment, perhaps by addressing psychological vulnerabilities specific to the population. The lack of significant differences at follow-up suggest that post-treatment contact may be needed to maintain advantages associated with this and similar interventions. Highlights: Adding a suicide-specific intervention to inpatient treatment may improve outcomes. Observed differences occurred across a range of clinical measures. Gains in two comparison groups were durable over a 6-month follow-up period. Trends toward superiority of CAMS at follow-up were not statistically significant.